Tantangan dan Pengelolaan Sejumlah Risiko Perbankan Syariah Era Digital - Muhlis Muhlis; Sudirman Sudirman (Al-Buhuts, 2021)
This paper aims to examine the challenges and management of banking in identifying and minimizing the impact of risks faced by banks today. The methodology used to construct this paper is through a literature review. This paper produces research that the complexity of the risks faced, both financial and non-financial risks, such as the operational risk of using modern technology services, which increasingly pampers millennial customers today in the world of financial institutions such as fintech. Advances in digital services such as neo bank, and the state of the pandemic. The competition for the use of technology, including banking, cannot be separated from the threat of crime risk, so it requires protection on the one hand. The irony is that banks that are unable to provide technology services will have difficulty competing. The outline of the risks faced in banking is not only financial but also non-financial. So it is urgent to be able to implement risk management in hedging banking, including Islamic banking, so that they can anticipate and then take the necessary actions in facing the competitive situation and conditions of the current era